2020
DOI: 10.1249/mss.0000000000002550
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Mobile 2D Imaging System for Body Volume and Subsequent Composition Estimates in a Three-Compartment Model

Abstract: Purpose: The purpose of the study was to compare a single two-dimensional image processing system (IMAGE) to underwater weighing (UWW) for measuring body volume (BV) and subsequently estimating body fat percentage (%Fat), fat mass (FM), and fat-free mass (FFM) via a 3-compartment (3C) model. Methods: A sample of participants age 18-39 yr was recruited for this study (n = 67, 47.8% female). BV was measured with UWW and predicted via the IMAGE software. The BV estimates from UWW (3C UWW ) and IMAGE (3C IMAGE ) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…The research regarding the validity of this new approach has begun to emerge. For instance, Fedewa et al recently demonstrated that body volume estimates from the same 2D method of the current study displayed an r of 0.99 when compared to the underwater weighing technique in a sample of healthy adults [ 10 ]. In addition, when the body volume estimates were combined with total body water measures from bioimpedance spectroscopy for a “field-based” three-compartment model, there were very large correlations (r = 0.96 to 0.99) with the laboratory method for FM and FFM [ 10 ].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The research regarding the validity of this new approach has begun to emerge. For instance, Fedewa et al recently demonstrated that body volume estimates from the same 2D method of the current study displayed an r of 0.99 when compared to the underwater weighing technique in a sample of healthy adults [ 10 ]. In addition, when the body volume estimates were combined with total body water measures from bioimpedance spectroscopy for a “field-based” three-compartment model, there were very large correlations (r = 0.96 to 0.99) with the laboratory method for FM and FFM [ 10 ].…”
Section: Discussionmentioning
confidence: 88%
“…For instance, Fedewa et al recently demonstrated that body volume estimates from the same 2D method of the current study displayed an r of 0.99 when compared to the underwater weighing technique in a sample of healthy adults [ 10 ]. In addition, when the body volume estimates were combined with total body water measures from bioimpedance spectroscopy for a “field-based” three-compartment model, there were very large correlations (r = 0.96 to 0.99) with the laboratory method for FM and FFM [ 10 ]. Moreover, Farina et al [ 26 ] showed no significant differences, strong relationships (R 2 = 0.91 to 0.95), and a small standard error of estimate values (±2.71 to 2.83 kg) when comparing FM estimates from a different 2D body composition program to dual-energy X-ray absorptiometry.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations